Improving Student Learning Outcomes Through the Application of Demonstration Methods in Science Learning At SMP Negeri 17 Palu - Murdiyah, Murdiyah (Universitas Negeri Makassar, 2023)
The demonstration method is a way of presenting lessons by demonstrating or demonstrating to students a particular process, situation, or object being studied, either actually or imitation, which is often accompanied by an oral explanation. With the demonstration method, the process of students' acceptance of the lesson will be more deeply impressive, thus forming a good and perfect understanding. Therefore, the aim of this research is to find out how the demonstration method is implemented so that it can improve the activities and learning outcomes of class IX A science lessons at SMP Negeri 17 Palu for the 2022/2023 academic year. The research method used is classroom action research. The research subjects consisted of 30 class IX A students, 17 boys and 13 girls at SMP Negeri 17 Palu. The research procedures carried out are based on each cycle, namely planning, implementation, observation, and reflection. Types of data and data collection techniques use qualitative and quantitative data, where qualitative data is collected through observation and documentation. Meanwhile, quantitative data is collected through tests at the end of each cycle. Meanwhile, data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. Data analysis techniques, namely qualitative and quantitative data analysis. The results of the research show that the application of the demonstration method can improve student learning outcomes in science learning class IX A of SMP Negeri 17 Palu in the 2022/2023 academic year.